(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to show the effect of the adoption of the concept of stakeholder management, good corporate governance and sustainable development on the development of the concept of corporate social responsibility (CSR) which then develops into the concept of corporate social responsiveness, corporate social performance and corporate citizenship. The research method used in this study uses literature studies since the beginning of the CSR concept formed in 1953 until the development of the CSR concept in the 2000s.The results showed that the dimensions of CSR consisting of economic responsibility, legal responsibility, ethical responsibility and discretional responsibility are still the main dimensions in the concept of corporate social responsiveness, corporate social performance and corporate citizenship. Research also shows that the adoption of the concept of stakeholder management, good corporate governance and sustainable development can optimize the implementation of CSR.